2021
DOI: 10.1159/000512628
|View full text |Cite
|
Sign up to set email alerts
|

Nonhormonal Treatment for Endometriosis Focusing on Redox Imbalance

Abstract: The aim of this review is to investigate the oxidant/antioxidant status and its regulatory mechanisms in patients with endometriosis and to summarize the antioxidant therapy as an alternative to hormonal therapy for endometriosis. Each keyword alone or in combination was used to search from PubMed and Embase by applying the filters of the title and the publication years between January 2000 and March 2020. Endometriosis is a chronic inflammatory disease characterized by repeated episodes of hemorrhage. Methemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 100 publications
(205 reference statements)
0
12
0
Order By: Relevance
“…Furthermore, RSV, like other polyphenols, has phytoestrogenic properties, that is, ability to bind and to affect steroid hormones receptors and to affect steroid‐dependent processes and diseases (Gambini et al, 2015; Nguyen, Savouret, Widerak, Corvol, & Rannou, 2017; Ortega & Duleba, 2015; van Duursen, 2017; Varoni, Lo Faro, Sharifi‐Rad, & Iriti, 2016; Zeng et al, 2020). RSV has antioxidant properties, which can be important in prevention of inflammation, malignant transformation and neurodegenerative diseases (Nagayasu, Imanaka, Kimura, Maruyama, & Kobayashi, 2021; Zeng et al, 2020). Moreover, RSV can bind and affect DNA methyltransferases and associated proteins responsible for DNA methylation resulting in activation of a number of genes (Mirza et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, RSV, like other polyphenols, has phytoestrogenic properties, that is, ability to bind and to affect steroid hormones receptors and to affect steroid‐dependent processes and diseases (Gambini et al, 2015; Nguyen, Savouret, Widerak, Corvol, & Rannou, 2017; Ortega & Duleba, 2015; van Duursen, 2017; Varoni, Lo Faro, Sharifi‐Rad, & Iriti, 2016; Zeng et al, 2020). RSV has antioxidant properties, which can be important in prevention of inflammation, malignant transformation and neurodegenerative diseases (Nagayasu, Imanaka, Kimura, Maruyama, & Kobayashi, 2021; Zeng et al, 2020). Moreover, RSV can bind and affect DNA methyltransferases and associated proteins responsible for DNA methylation resulting in activation of a number of genes (Mirza et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Dual role of antioxidants in the different stages of malignant transformation of endometriosis. Nagayasu et al (34) presented a comprehensive review on the endogenous antioxidant defense systems in endometriosis. The generated ROS can be scavenged by enzymatic (e.g., superoxide dismutase [SOD], catalase, reduced glutathione [GSH], glutathione peroxidase [GPX], and thioredoxin) and non-enzymatic (e.g., estradiol, melatonin, vitamin E, and vitamin C) antioxidants (35,36).…”
Section: Current Understanding Of Malignant Transformation Of Endomet...mentioning
confidence: 99%
“…Curcumin can significantly reduce the expression of COX-2, the production of TNF-α and IL-6, and decrease the epithelium-mesenchymal transition, essential for the development of endometriosis [64,108]. In addition, it can also reduce cell proliferation, decrease the size of endometriotic lesions, generate a reduction in matrix metalloproteinase-9 activity, and reduce VEGF expression, thus having an antiangiogenic character [126]. Chowdhury and collaborators demonstrated in their study that the effects of curcumin treatment on eutopic endometrial cells from endometriosis patients significantly reduce the secretion of inflammatory cytokines in these cells, also decreasing the phosphorylation of IKKα/β, NF-κB, STAT3, and JNK signaling pathways [127].…”
Section: Curcuminmentioning
confidence: 99%
“…Puerarin is an isoflavonoid found in Pueraria lobata, used in the treatment of cardiovascular and neurological diseases. Due to its ability to inhibit aromatase enzyme activity in endometrial cells and suppress cell adhesion and proliferation, it constitutes a possible new treatment against endometriosis [126,128]. A study by Yu et al [129] showed that treatment with puerarin reduced the levels of estradiol and PGE2 in endometriotic rats, by inhibiting the aromatase enzyme P450 and COX-2, in addition to increasing the expression of 17β-HSD2, thus preventing the growth of endometrial tissue.…”
Section: Puerarinmentioning
confidence: 99%
See 1 more Smart Citation